2020
DOI: 10.3390/vaccines8040722
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination during the First Diagnosis of Multiple Myeloma: A Cohort Study of the French National Health Insurance Database

Abstract: Purpose: Infections are frequent and often result in serious complications in patients with multiple myeloma (MM). Prophylactic vaccination is recommended for influenza virus, Streptococcus pneumoniae (SP), and Hemophilus influenzaeb (Hib). The aims of this study were to measure the vaccination rates within 24 months after the diagnosis of multiple myeloma and to identify factors associated with vaccine use. Methods: MM patients were selected through the French national health insurance database from 1 January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…A recent analysis of the "Surveillance, Epidemiology, and End Results-Medicare" database (https://seer.cancer.gov/, accessed on 4 October 2021) showed that only 64% of older adults with active MM received bonemodifying agents, 52% an influenza vaccination, and less than 50% antiviral prophylaxis during treatment with PI [144]. Similarly, a French study reported very low rates of vaccination for influenza (28%) in MM patients, with less than 1% of the patients receiving all three recommended vaccines (influenza, Streptococcus pneumoniae, and Hemophilus influenzae) [145]. The frequent risk factors for the underutilization of recommended care are older age, higher comorbidity burden, and care in the community setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of the "Surveillance, Epidemiology, and End Results-Medicare" database (https://seer.cancer.gov/, accessed on 4 October 2021) showed that only 64% of older adults with active MM received bonemodifying agents, 52% an influenza vaccination, and less than 50% antiviral prophylaxis during treatment with PI [144]. Similarly, a French study reported very low rates of vaccination for influenza (28%) in MM patients, with less than 1% of the patients receiving all three recommended vaccines (influenza, Streptococcus pneumoniae, and Hemophilus influenzae) [145]. The frequent risk factors for the underutilization of recommended care are older age, higher comorbidity burden, and care in the community setting.…”
Section: Discussionmentioning
confidence: 99%